High and Low Affinity Heparin Compared with Unfractionated Heparin as Antithrombotic Drugs - Merton, R E; Thomas, D P; Havercroft, S J; Barrowcliffe, T W; Lindahl, U (Thrombosis and Haemostasis, 1984)
A preparation of heparin was separated by affinity chromatography into two fractions: one of high (HAH) and the other of low (LAH) affinity to antithrombin III. These two fractions were compared with unfractionated heparin (UFH) by in vitro assay and their ability to impair experimental stasis thrombosis was also examined. Although the in vitro activity of HAH was double that of UFH, HAH was less effective than UFH as an antithrombotic drug; LAH was virtually inactive, both in vitro and in vivo. A mixture of 30 μg/kg of HAH and 50 μg/kg of LAH was as effective in preventing thrombosis as 80 μg/kg of UFH, and was more effective than 40 μg/kg of HAH alone, demonstrating that LAH potentiates the action of HAH in vivo.
Keywords: High affinity heparin; Low affinity heparin; Venous thrombosis